The Efficacy and Duration of Protection of Pneumococcal Conjugate Vaccines Against Nasopharyngeal Carriage - Olivier le Polain de Waroux; Stefan Flasche; David Prieto‐Merino; David Goldblatt; W. John Edmunds (2015)
Pneumococcal conjugate vaccines (PCVs) reduce disease largely through their impact on nasopharyngeal (NP) carriage acquisition of Streptococcus pneumoniae, a precondition for developing any form of pneumococcal disease. We aimed to estimate the vaccine efficacy (VEC) and duration of protection of PCVs against S. pneumoniae carriage acquisition through meta-regression models.We identified intervention studies providing NP carriage estimates among vaccinated and unvaccinated children at any time after completion of a full vaccination schedule. We calculated VEC for PCV7 serotypes, grouped as well as individually, and explored cross-protective efficacy against 6A. Efficacy estimates over time were obtained using a Bayesian meta-logistic regression approach, with time since completion of vaccination as a covariate.We used data from 22 carriage surveys (15 independent studies) from 5 to 64 months after the last PCV dose, including 14,298 children. The aggregate VEC for all PCV7 serotypes 6 months after completion of the vaccination schedule was 57% (95% credible interval: 50-65%), varying by serotype from 38% (19F) to 80%. Our model provides evidence of sustained protection of PCVs for several years, with an aggregate VEC of 42% (95% credible interval: 19-54%) at 5 years, although the waning differed between serotypes. We also found evidence of cross-protection against 6A, with a VEC of 39% 6 months after a complete schedule, decreasing to 0 within 5 years postvaccination.Our results suggest that PCVs confer reasonable protection against acquisition of pneumococcal carriage of the 7 studied serotypes, for several years after vaccination, albeit with differences across serotypes.